T cell epitopes of SARS-CoV-2 spike protein and conserved surface protein of Plasmodium malariae share sequence homology - Hassan Md. Mehedi (De Gruyter, 2021)
Since its emergence in late 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been spreading remarkably fast worldwide. Effective countermeasures require the rapid development of data and tools to monitor its spread and better understand immunogenic profile. However, limited information is available about the tools and target of the immune responses to SARS-CoV-2. In this study, we excogitated a new approach for analyzing phylogenetic relationships by using the whole prototype proteome sequences. Phylogenetic analysis on the whole prototype proteome sequences showed that SARS-CoV-2 was a direct descendant of Bat-CoV and was closely related to Pangolin-CoV, Bat-SL-CoV, and SARS-CoV. The pairwise comparison of SARS-CoV-2 with Bat-CoV showed an unusual replacement of the motif consisting of seven amino acids (NNLDSKV) within the spike protein of SARS-CoV-2. The replaced motif in the spike protein of SARS-CoV-2 was found in 12 other species, including a conserved surface protein of a malaria-causing pathogen, Plasmodium malariae. We further identified the T and B cell epitope sequence homology of SARS-CoV-2 spike protein with conserved surface protein of P. malariae using the Immune Epitope Database and Analysis Resource (IEDB). The shared immunodominant epitopes may provide immunity against SARS-CoV-2 infection to those previously infected with P. malariae.